Application Of The Fuzzy Min-Max Neural Networks To Medical Diagnosis. - Quteishat, Anas Mohammad Ali; Chee, Peng Lim (2008)

(untitled)
Abstract. In this paper, the Fuzzy Min-Max (FMM) neural network along with two modified FMM models are used for tackling medical diagnostic problems. The original FMM network establishes hyperboxes with fuzzy sets in its structure for classifying input patterns into different output categories.